(untitled) (Movimento-revista de educação, 2017)
O artigo realiza um diálogo com alguns historiadores ambientais, tendo como foco a história da Mata Atlântica, demonstrando a pertinência de revermos criticamente os padrões de produção e de apropriação dos recursos naturais, desde a pré-história até o período colonial no Brasil. Recuperando historicamente as relações das diferentes formações sociais com a floresta, compreende-se o caráter predatório dos impactos socioambientais resultantes do projeto colonizador português em nosso país. Palavras-chave: Mata Atlântica; História Ambiental; Ensino de História. THE ATLANTIC FOREST AND THE TEACHING OF HISTORY: from prehistory to brazilian colonial period Abstract The article conducts a dialogue with some environmental historians with a focus on the history of the Atlantic Forest, demonstrating the relevance of critically reviewing the patterns of production and appropriation of natural resources, from prehistoric times to the colonial period in Brazil. By recovering historically the relationship between the forest and different social formations, we can understand the predatory nature of socio-environmental impacts resulting from the Portuguese colonial project in our country. Keywords: Atlantic Forest; Environmental History; History Teaching.